Awareness of stroke among patients with chronic kidney disease on hemodialysis: a cross-sectional study - Gomes, Orlando Vieira; Guimarães, Manoel Pereira; Barbosa, Bárbara Maria Batista; Marinho, Christielle Lidianne Alencar; Nicacio, Jandir Mendonça; Barreira, Matheus Pereira; Rodrigues, Mateus de Sousa; Santana, Leonardo Fernandes e; Elihimas Júnior, Ubiracé Fernando; Schwingel, Paulo Adriano (São Paulo Medical Journal, 2025)
BACKGROUND: Stroke is a major cause of mortality worldwide. Renal dysfunction is an important risk factor for stroke. Brazilian studies on stroke knowledge are generally population based. Studies stratifying stroke knowledge according to comorbidities are rare. Scientific data are essential to guide the awareness of stroke. OBJECTIVE: To assess stroke knowledge in patients with chronic kidney disease (CKD) on hemodialysis. DESIGN AND SETTING: Cross-sectional analytical study of patients with CKD on hemodialysis in northeastern Brazil. METHODS: A self-administered questionnaire survey on stroke awareness was administered to patients with CKD on hemodialysis between April and November 2022. The chi-square test and other descriptive statistics were used. Univariate and multivariate analyses were performed using logistic regression. RESULTS: A total of 197 patients were included in the analysis. The Brazilian acronym for stroke was used by 53.5% of the participants. Less than 10.0% of the sample showed optimal decision-making ability regarding stroke. Of the participants, 29.9% knew at least one risk factor and one symptom; however, this was considered as having below the minimum capacity because they did not know the emergency service call number. In the analysis adjusted for income and education, females (odds ratio [OR], 0.40%; 95% confidence interval [CI], 0.20–0.82), older patients (OR, 0.24%; 95% CI, 0.09–0.63) and having at most one comorbidity (OR, 0.48%; 95% CI, 0.23–0.98) were factors for lower levels of knowledge or ideal decision-making capacity against stroke. CONCLUSIONS: Patients on hemodialysis, especially women and older people, have little knowledge about stroke.